Game analysis of price war among merchants in the coffee market - Wang Zhuling (SHS Web of Conferences)
In recent years, with the improvement of the national economy, the improvement of living standards and the deepening of people’s understanding of coffee culture, China’s coffee market has entered a period of rapid development. The number of coffee brands and chain stores has increased rapidly, and coffee culture has gradually integrated into people’s daily lives. In order to better and faster occupy the domestic coffee market, the two major coffee giants Luckin Coffee and Kudi have chosen price war as their main strategy. This study uses the prisoner’s dilemma, the Bertrand model and repeated games to analyze the price game competition behavior between enterprises, and explores how enterprises can more effectively deal with the risks of price wars and reduce the negative impact of price wars. The results show that enterprises can enhance their market competitiveness through non-price competition (such as product differentiation, brand building, customer loyalty, etc.), and at the same time stabilize market prices through cooperation and tacit understanding to ensure the long-term sustainable development of enterprises. The effectiveness of these methods has been tested, and relevant strategic recommendations have been put forward.